Electrode material for electrocatalytic degradation of organic wastewater containing high-concentration nitrate and application of electrode material

By preparing Ti/Cu-Sn multimetallic coating electrode material, it is used to electrochemically catalytically degrade industrial wastewater containing high concentrations of nitrates and organics, the problems of low removal efficiency and by-product pollution in traditional methods are solved, and efficient, economical and environmentally friendly wastewater treatment is achieved, and hydrogen is produced in co-product.

CN119591204AActive Publication Date: 2025-03-11FUZHOU UNIV

Patent Information

Application Number
CN202411835512.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

It is difficult for the prior art to efficiently remove industrial wastewater containing high concentrations of nitrates and organic matter. Traditional electrochemical denitrification methods have problems such as low nitrogen selectivity, poor electrode stability and by-product pollution.

Method used

Ti plates are used as substrates and high-temperature calcination is carried out through copper nitrate and metal tin salt precursor solutions to prepare Ti/Cu-Sn multi-metal coating electrode material for electrochemical catalytic degradation of organic wastewater containing high concentrations of nitrate and hydrogen production in conjunction.

Benefits of technology

Safe, efficient and green nitrate and organic matter removal has been achieved. The nitrate removal rate can reach 99.72%, COD removal rate can reach 84.61%, nitrogen selectivity can reach 99.83%, and hydrogen is produced at the same time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses an electrode material for electrocatalytic degradation of organic wastewater containing high-concentration nitrate and application of the electrode material, a copper salt precursor solution and a tin salt precursor solution are sequentially attached to the surface of a Ti plate, so that a Ti / Cu-Sn multi-metal coating electrode material is obtained, the Ti / Cu-Sn multi-metal coating electrode material is used as a cathode, a metal electrode is used as an anode to construct an electrolytic tank, and the high-concentration nitrate-containing organic wastewater is obtained. The catalyst is used for simultaneous degradation of NO3 <-> and COD in organic wastewater containing high-concentration nitrate and co-production of hydrogen. The electrode material is simple in preparation process, low in cost and high in catalytic activity and stability, nitrate and organic matter in wastewater can be safely, mildly and simultaneously removed in the electrolysis process of the electrode material, and secondary pollution byproducts such as ammonia nitrogen and nitrite are hardly generated. Tests show that the removal rate of nitrate radicals can reach 99.72%, the removal rate of COD (Chemical Oxygen Demand) can reach 84.61% and the selectivity of nitrogen can reach 99.83% when the method is used for treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical sewage treatment, and specifically relates to an electrode material for electrocatalytic degradation of organic wastewater containing high-concentration nitrate and application thereof. Background Art

[0002] In the process of preparing silver powder by liquid phase reduction method, industrial silver powder wastewater containing extremely high concentrations of nitrate and COD will be produced. It is difficult to treat and has a huge impact on the water circulation system in the ecological environment. In addition, high concentrations of nitrate in drinking water are very harmful to the human body. Therefore, the development of efficient and economical nitrate removal technology has great practical significance. At present, the treatment methods for nitrate in wastewater include the following: biological denitrification, ion exchange, reverse osmosis, chemical catalysis and electrochemical catalysis. Among them, the electrochemical catalysis method has the advantages of high reaction efficiency, high selectivity and environmental friendliness compared with other methods, but it also has disadvantages such as high energy consumption and the production of a large amount of ammonia nitrogen, which need to be solved urgently.

[0003] At the same time, the current technologies for removing organic matter from wastewater mainly include activated carbon adsorption, chemical adsorbent adsorption, Fenton oxidation, and Fenton-like oxidation. Among them, Fenton-like oxidation is widely used due to its mild reaction conditions and high catalytic efficiency. Among the Fenton-like oxidation methods, the most widely used technologies include electrocatalytic oxidation, ozone catalytic oxidation, and hydrogen peroxide catalytic oxidation. Among them, electrocatalytic oxidation technology is favored by researchers due to its super strong oxidizing properties and catalytic stability.

[0004] However, although electrochemical technology has been reported to be used to treat organic wastewater and wastewater containing nitrates, there is still a lack of research on the treatment of industrial wastewater containing both organic matter and nitrates. In addition, traditional electrochemical denitrification methods have problems such as low nitrogen selectivity, poor electrode stability, and the generation of ammonia nitrogen byproducts that pollute the environment. Summary of the invention

[0005] In view of the above problems, the present invention proposes an electrode material for electrocatalytic degradation of organic wastewater containing high concentration of nitrate and its application.

[0006] Specifically, the first object of the present invention is to provide a method for preparing a catalyst having a simple preparation process, low cost and can be used for electrocatalytic degradation of NO3 - And COD electrode materials.

[0007] The second object of the present invention is to provide an electrochemical method for simultaneously removing nitrates and organic matter in a safe, efficient and green manner and capable of co-producing hydrogen.

[0008] To achieve the above object, the present invention adopts the following technical solutions: A cathode material for catalytic degradation of organic wastewater containing high concentration of nitrates, the preparation of which comprises the following steps: 1) After the Ti plate is polished with sandpaper, it is first placed in a 10 wt% NaOH solution to heat and remove oil, and then placed in a 10 wt% oxalic acid solution to heat and etch the surface; 2) Apply the copper salt precursor solution evenly to the surface of the etched Ti plate, dry it and then bake it; repeat this process 6 times, rinse it with deionized water and anhydrous ethanol in turn, and wipe the surface with filter paper to ensure that no coating falls off; 3) Using the tin salt precursor solution, the Ti / Cu-Sn multi-metal coating electrode material is prepared according to step 2).

[0009] Furthermore, the heating temperature in step 1) is 60-90°C and the heating time is 30-180 min.

[0010] Furthermore, the copper salt precursor solution in step 2) is specifically an ethanol solution of copper nitrate, the concentration of which is 0.1-2 mol / L, and the application amount is 0.08 mL / cm 2 .

[0011] Furthermore, the drying temperature in step 2) is 60-120°C and the drying time is 10-60 min.

[0012] Furthermore, in step 2), the calcination temperature is 250-850°C and the calcination time is 10-60 min.

[0013] Furthermore, the amount of the tin salt precursor solution applied in step 3) is 0.04 mL / cm 2 The method comprises mixing metal tin salt, sodium hypophosphite, thiourea, a complexing agent and concentrated hydrochloric acid, heating and stirring at 60-100°C for 5-45 minutes to make the mixture uniformly mixed, and then cooling the mixture, wherein the concentrations of the metal tin salt, sodium hypophosphite, thiourea, the complexing agent and the concentrated hydrochloric acid are 0.05-2 mol / L, 0.5-3 mol / L, 0.05-1.5 mol / L, 0.01-1 mol / L and 0.1-1 mol / L, respectively.

[0014] Furthermore, the metal tin salt is selected from one of stannous chloride, stannous chloride, trimethyltin chloride and stannous sulfate.

[0015] Furthermore, the complexing agent is selected from one of sodium citrate, ascorbic acid, sodium bicarbonate and glucose.

[0016] The electrode material can be used for electrochemical catalytic degradation of organic wastewater containing high concentration of nitrate, such as industrial silver powder wastewater.

[0017] Specifically, the application method is to use the electrode material as the cathode to construct an electrolytic cell, - Under the conditions, it is used in NO3 - And COD is degraded simultaneously, and hydrogen is produced in conjunction.

[0018] Furthermore, the electrolytic cell uses one of a Pt electrode, an iridium-tantalum-titanium electrode, a ruthenium-iridium-titanium electrode, and a nickel plate electrode as the anode.

[0019] Furthermore, during electrolysis, 1-12 mol / L HCl solution was used to adjust the pH of the waste liquid to 0.5-3 and the conductivity to 15-45 mS / cm, so that the Cl - .

[0020] Furthermore, the NO3 in the wastewater - Concentration ≤10000 mg / L, COD concentration ≤5000 mg / L.

[0021] The present invention uses Ti plate as a substrate, copper nitrate solution and metal tin salt solution as precursor solutions, and produces Ti / Cu-Sn multi-metal coating electrode materials by a high-temperature roasting method. Compared with other electrolytic wastewater denitrification electrodes, the synthesis method is simple and the production cost is low. At the same time, it has higher catalytic activity and stability, and also has higher catalytic activity in the field of electrocatalytic reduction of carbon dioxide.

[0022] The present invention uses Ti / Cu-Sn as a cathode and a metal electrode as an anode to construct an electrolytic cell for electrolytic denitrification of organic wastewater containing high-concentration nitrates, wherein chloride ions can oxidize ammonia nitrogen generated by nitrate degradation into nitrogen gas at the anode, and simultaneously remove nitrates and co-produce hydrogen at the cathode, and remove organic matter at the anode. This new electrochemical denitrification method not only avoids the pollution of the environment by byproducts, but also simplifies the wastewater treatment process of multiple pollution sources.

[0023] The beneficial effects of the present invention are as follows: 1) Low cost and multiple application fields of electrodes. No reagent is required in the preparation process of the electrode of the present invention, the power consumption is low, the materials used for the electrode are all non-precious metal materials, and it can also be applied to the field of electrocatalytic reduction of carbon dioxide.

[0024] 2) The method is simple and green. Compared with the existing multiple-effect evaporation method, biological denitrification method and other methods, the present invention adopts electrochemical catalysis for degradation, which does not require additional energy-consuming processes, does not produce secondary pollutants, and has simpler facilities and equipment.

[0025] 3) The performance is impressive and hydrogen can be co-produced. By using Ti / Cu-Sn as the cathode and the metal electrode as the anode, the chloride ions can be oxidized at the anode to oxidize the ammonia nitrogen generated by the degradation of nitrates into nitrogen, and at the same time, nitrates are removed at the cathode and hydrogen is co-produced, and organic matter is removed at the anode. According to the test, the nitrate removal rate can reach 99.72%, the COD removal rate can reach 84.61%, and the nitrogen selectivity can reach 99.83%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The nitrate conversion and organic matter removal rate obtained by electrochemically catalytically degrading organic wastewater containing high concentration of nitrate using the Ti / Cu-Sn cathode prepared in Example 1.

[0027] Figure 2 The nitrate concentration and removal rate obtained by electrochemically catalytically degrading organic wastewater containing high concentration of nitrate using the Ti / Cu-Sn cathode prepared in Example 1 vary with time.

[0028] Figure 3 This is a comparison chart of nitrate removal rates obtained by electrochemically catalytically degrading organic wastewater containing high-concentration nitrate using the cathodes prepared in Example 1 and Comparative Examples 2-4. DETAILED DESCRIPTION

[0029] A cathode material for catalytic degradation of organic wastewater containing high concentration of nitrates, the preparation of which comprises the following steps: 1) After the Ti plate was polished with sandpaper of different coarseness and fineness, it was first placed in a 10 wt% NaOH solution and heated at 60-90 °C for 30-180 min for degreasing, and then placed in a 10 wt% oxalic acid solution and heated at 60-90 °C for 30-180 min for surface etching; 2) Mix 0.1~2 mol / L copper nitrate ethanol solution at 0.08 mL / cm 2 Apply the amount of coating evenly to the etched Ti plate surface, dry at 60-120 °C for 10-60 min, and bake at 250-850 °C for 10-60 min. Repeat this process 6 times, rinse with deionized water and anhydrous ethanol in turn, and wipe the surface with filter paper to ensure that no coating falls off. 3) Mix metal tin salt, sodium hypophosphite, thiourea, chelating agent and concentrated hydrochloric acid (36.5 wt%), heat and stir at 60-100 °C for 5-45 min to mix well, and then cool to prepare a tin salt precursor solution, wherein the concentrations of metal tin salt, sodium hypophosphite, thiourea, chelating agent and concentrated hydrochloric acid are 0.05-2 mol / L, 0.5-3 mol / L, 0.05-1.5 mol / L, 0.01-1 mol / L and 0.1-1 mol / L, respectively; then use the tin salt precursor solution at 0.04 mL / cm 2 Apply an amount of and operate according to step 2) to prepare a Ti / Cu-Sn multi-metal coating electrode material.

[0030] The metal tin salt is selected from stannous chloride, tin chloride, trimethyltin chloride, and stannous sulfate. The complexing agent is selected from sodium citrate, ascorbic acid, sodium bicarbonate, and glucose.

[0031] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0032] The Pt anode, ruthenium-iridium-titanium anode, iridium-tantalum-titanium anode and nickel plate anode used in the examples were all purchased from Suzhou Shultai Industrial Technology Co., Ltd.

[0033] Example 1 (1) The Ti plate (5 cm × 5 cm) was polished with sandpaper of different coarseness and fineness, and then placed in 10 wt% NaOH solution and 10 wt% oxalic acid solution, respectively, and heated in a water bath at 60-90 °C for 30 min and then taken out for use; (2) Weigh a certain amount of copper nitrate trihydrate and dissolve it in ethanol to prepare a 2 mol / L copper nitrate precursor solution; weigh a certain amount of metal tin salt, sodium hypophosphite, thiourea, complexing agent sodium citrate and concentrated hydrochloric acid (36.5 wt%), put them into a magnetic stirrer and heat them to 60°C, stir them for 10 min, and let the solution stand after cooling to room temperature to obtain a metal tin salt precursor solution, in which the contents of each component are: 0.05 mol / L stannous chloride, 0.5 mol / L sodium hypophosphite, 0.05 mol / L thiourea, 0.01 mol / L sodium citrate and 0.1 mol / L concentrated hydrochloric acid; (3) 8 mL of the prepared copper nitrate precursor solution was evenly applied to the surface of the Ti plate, placed in a 120 °C oven for drying for 10 min, and then placed in a 650 °C box-type electric furnace for baking for 15 min; after repeating this process 6 times, it was placed in a 650 °C box-type electric furnace for baking for 1 h. After taking it out, it was rinsed with deionized water and anhydrous ethanol in turn and the surface was wiped with filter paper to ensure that no coating fell off; then the precursor solution was replaced with 4 mL of the prepared metal tin salt precursor solution and applied and the above process was repeated to finally obtain a Ti / Cu-Sn cathode; (4) Add 200 mL of high-concentration nitrate-organic wastewater (NO3 - -N=10000 mg / L, COD=5000 mg / L, NH4 + -N=1000 mg / L) was added with a certain amount of 12 mol / L HCl solution to adjust the pH value and conductivity to 0.5 and 45 mS / cm respectively; then the wastewater, the prepared Ti / Cu-Sn cathode, the Pt anode and the rotor were placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the distance between the electrode plates was adjusted to 4 mm, the speed of the magnetic stirrer was set to 650 rpm, the DC power supply was turned on, and the current density was set to 25 mA / cm 2 The reaction started after 10 hours. The nitrate and COD in the waste liquid were detected (the nitrate detection method refers to GB / T 6912.1-2006, and the COD detection method refers to HJ / T 399-2007). The nitrate removal rate was 99.72%, the COD removal rate was 84.61%, and the nitrogen selectivity was 99.83%.

[0034] Example 2 (1) The Ti plate (5 cm × 5 cm) was polished with sandpaper of different coarseness and fineness, and then placed in 10 wt% NaOH solution and 10 wt% oxalic acid solution, respectively, and heated in a water bath at 60-90 °C for 180 min and then taken out for use; (2) Weigh a certain amount of copper nitrate trihydrate and dissolve it in ethanol to prepare a 1 mol / L copper nitrate precursor solution; weigh a certain amount of metal tin salt, sodium hypophosphite, thiourea, chelating agent ascorbic acid and concentrated hydrochloric acid (36.5 wt%), put them into a magnetic stirrer and heat and stir them, and let the solution stand after cooling to room temperature to obtain a metal tin salt precursor solution, in which the contents of the components are: 2 mol / L tin chloride, 3 mol / L sodium hypophosphite, 1.5 mol / L thiourea, 1 mol / L ascorbic acid and 1 mol / L concentrated hydrochloric acid; (3) 8 mL of the prepared copper nitrate precursor solution was evenly applied to the surface of the Ti plate, placed in a 90 °C oven for drying for 15 min, and then placed in a 250 °C box-type electric furnace for baking for 10 min; after repeating this process 6 times, it was placed in a 250 °C box-type electric furnace for baking for 1 h. After taking it out, it was rinsed with deionized water and anhydrous ethanol in turn and the surface was wiped with filter paper to ensure that no coating fell off; then the precursor solution was replaced with 4 mL of the prepared metal tin salt precursor solution and the above process was repeated to finally obtain a Ti / Cu-Sn cathode; (4) Add 1000 mL of high concentration nitrate-organic wastewater (NO3 - -N=100 mg / L, COD=100mg / L, NH4 + -N=100 mg / L) was added with a certain amount of 10 mol / L HCl solution to adjust the pH value and conductivity to 1.5 and 30 mS / cm, respectively; the wastewater, the prepared Ti / Cu-Sn cathode, the iridium-tantalum-titanium anode and the rotor were then placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the distance between the electrode plates was adjusted to 20 mm, the speed of the magnetic stirrer was set to 150 rpm, the DC power supply was turned on, and the current density was set to 20 mA / cm 2 The reaction started after that. After 5 hours, the nitrate and COD in the waste liquid were detected (the nitrate detection method refers to "GB / T 6912.1-2006", and the COD detection method refers to "HJ / T 399-2007"). The nitrate removal rate was 98.81%, the COD removal rate was 72.71%, and the nitrogen selectivity was 98.13%.

[0035] Example 3 (1) The Ti plate (5 cm × 5 cm) was polished with sandpaper of different coarseness and fineness, and then placed in 10 wt% NaOH solution and 10 wt% oxalic acid solution, respectively, and heated in a water bath at 60-90 °C for 120 min and then taken out for use; (2) Weigh a certain amount of copper nitrate trihydrate and dissolve it in ethanol to prepare a 0.1 mol / L copper nitrate precursor solution; weigh a certain amount of metal tin salt, sodium hypophosphite, thiourea, chelating agent sodium bicarbonate and concentrated hydrochloric acid (36.5 wt%), put them into a magnetic stirrer and heat and stir them, and let the solution stand after cooling to room temperature to obtain a metal tin salt precursor solution, in which the contents of each component are: 1 mol / L trimethyltin chloride, 2 mol / L sodium hypophosphite, 1 mol / L thiourea, 0.5 mol / L sodium bicarbonate and 0.5 mol / L concentrated hydrochloric acid.

[0036] (3) 8 mL of the prepared copper nitrate precursor solution was evenly applied to the surface of the Ti plate, placed in a 60 °C oven for drying for 60 min, and then placed in a box-type electric furnace at 850 °C for 60 min; after repeating this process 6 times, it was placed in an 850 °C box-type electric furnace for 1 h. After taking it out, it was rinsed with deionized water and anhydrous ethanol in turn and the surface was wiped with filter paper to ensure that no coating fell off; then the precursor solution was replaced with 4 mL of the prepared metal tin salt precursor solution and applied and the above process was repeated to finally obtain a Ti / Cu-Sn cathode; (4) Add 250 mL of high-concentration nitrate-organic wastewater (NO3 - -N=5000 mg / L, COD=3000mg / L, NH4 + -N=500 mg / L) was added with a certain amount of 1 mol / L HCl solution to adjust the pH value and conductivity to 3 and 15 mS / cm, respectively; then the wastewater, the prepared Ti / Cu-Sn cathode, the ruthenium-iridium-titanium anode and the rotor were placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the distance between the electrode plates was adjusted to 6 mm, the speed of the magnetic stirrer was set to 450 rpm, the DC power supply was turned on, and the current density was set to 50 mA / cm 2 The reaction started after that, and after 1 hour, the nitrate and COD in the waste liquid were detected (the nitrate detection method refers to "GB / T 6912.1-2006", and the COD detection method refers to "HJ / T 399-2007"). The nitrate removal rate was 95.65%, the COD removal rate was 75.29%, and the nitrogen selectivity was 95.77%.

[0037] Example 4 (1) The Ti plate (5 cm × 5 cm) was polished with sandpaper of different coarseness and fineness, and then placed in 10 wt% NaOH solution and 10 wt% oxalic acid solution, respectively, and heated in a water bath at 60-90 °C for 120 min and then taken out for use; (2) Weigh a certain amount of copper nitrate trihydrate and dissolve it in ethanol to prepare a 1 mol / L copper nitrate trihydrate precursor solution; weigh a certain amount of metal tin salt, sodium hypophosphite, thiourea, chelating agent glucose and concentrated hydrochloric acid (36.5 wt%), put them into a magnetic stirrer and heat and stir them, and let the solution stand after cooling to room temperature to obtain a metal tin salt precursor solution, in which the contents of each component are: 1 mol / L stannous sulfate, 1 mol / L sodium hypophosphite, 1.25 mol / L thiourea, 0.5 mol / L glucose and 0.5 mol / L concentrated hydrochloric acid.

[0038] (3) 8 mL of the prepared copper nitrate precursor solution was evenly applied to the surface of the Ti plate, placed in a 95 °C oven for drying for 15 min, and then placed in a 650 °C box-type electric furnace for baking for 15 min; after repeating this process 6 times, it was placed in a 650 °C box-type electric furnace for baking for 1 h. After taking it out, it was rinsed with deionized water and anhydrous ethanol in turn and the surface was wiped with filter paper to ensure that no coating fell off; then the precursor solution was replaced with 4 mL of the prepared metal tin salt precursor solution and the above process was repeated to finally obtain a Ti / Cu-Sn cathode; (4) Add 450 mL of high-concentration nitrate-organic wastewater (NO3 - -N=2000 mg / L, COD=500mg / L, NH4 + -N=250 mg / L) was added with a certain amount of 6 mol / L HCl solution to adjust the pH value and conductivity to 1.5 and 25 mS / cm respectively; then the wastewater, the prepared Ti / Cu-Sn cathode, the nickel plate anode and the rotor were placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the distance between the electrode plates was adjusted to 6 mm, the speed of the magnetic stirrer was set to 500 rpm, the DC power supply was turned on, and the current density was set to 5 mA / cm 2 The reaction started after that. After 3 hours, the nitrate and COD in the waste liquid were detected (the nitrate detection method refers to GB / T 6912.1-2006, and the COD detection method refers to HJ / T 399-2007). The nitrate removal rate was 96.61%, the COD removal rate was 70.34%, and the nitrogen selectivity was 96.02%.

[0039] Example 5 In order to further verify the feasibility of Ti / Cu-Sn electrode in the field of electrocatalytic reduction of carbon dioxide, the Ti / Cu-Sn electrode prepared in Example 1 was used for electrocatalytic reduction of carbon dioxide experiment. The experiment was carried out using Chenhua CHI-1140C electrochemical workstation, which was connected to an H-type electrolytic cell with a three-electrode system. The working electrode, reference electrode and counter electrode used were Ti / Cu-Sn (5×5 cm 2 ), Ag / AgCl electrode and Pt electrode (3×3 cm 2 ), the anode and cathode chambers of the H-type electrolytic cell were separated by a Nafion-117 ion exchange membrane, the electrolyte was 0.5 M KHCO3, the gas flow rate was 20 sccm, and the reaction was carried out at a potential of -1.0 V vs. RHE for 90 min. The Faradaic efficiencies of the products were: HCOOH=30.45%, H2=52.29%, and CO=16.44%.

[0040] Comparative Example 1 In order to verify the effect of chloride ions on the oxidation of ammonia nitrogen, in this comparative example, no HCl solution was added before the electrolytic denitrification began. Specifically, 200 mL of high-concentration nitrate-organic wastewater (NO3 - -N=10000 mg / L, COD=5000 mg / L, NH4 + -N=1000 mg / L) was added with a certain amount of 1 mol / L sulfuric acid solution, and the pH value and conductivity were adjusted to 0.5 and 45 mS / cm respectively; the other electrolysis conditions were the same as those in Example 1, and the nitrate and COD in the waste liquid were detected after 10 hours (the nitrate detection method refers to GB / T 6912.1-2006, and the COD detection method refers to HJ / T 399-2007). The nitrate removal rate was 90.76%, the COD removal rate was 65.41%, and the nitrogen selectivity was 5.35%. It can be seen that Cl - The ions will convert the generated ammonia nitrogen into nitrogen gas during the electrolysis process, so their presence greatly improves the nitrogen selectivity without affecting the removal effect of nitrate and COD.

[0041] Comparative Example 2 In order to verify the effect of Sn coating on the electrolytic denitrification performance, in this comparative example, only the Ti plate was subjected to the synthesis treatment of Cu coating, and the specific operation steps were consistent with those in Example 2. Then, 1000 mL of high-concentration nitrate-organic wastewater (NO3 - -N=100 mg / L, COD=100mg / L, NH4 + -N=100 mg / L) was added with a certain amount of 10 mol / L HCl solution to adjust the pH value and conductivity to 1.5 and 30 mS / cm, respectively; the wastewater, the prepared Ti / Cu cathode, the iridium-tantalum-titanium anode and the rotor were then placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the distance between the electrode plates was adjusted to 20 mm, the speed of the magnetic stirrer was set to 150 rpm, the DC power supply was turned on, and the current density was set to 20 mA / cm 2 After that, the reaction started. After 5 hours, the nitrate and COD in the waste liquid were detected (the nitrate detection method refers to GB / T 6912.1-2006, and the COD detection method refers to HJ / T 399-2007). Finally, the nitrate removal rate was 54.36%, the COD removal rate was 71.88%, and the nitrogen selectivity was 95.23%. It can be seen that the nitrate removal rate of the Ti / Cu coated electrode is significantly lower than that of the Ti / Cu-Sn used in Example 2, proving that the Cu / Sn bimetallic coating has a unique performance effect on electrolytic denitrification.

[0042] Comparative Example 3 In order to verify the effect of Cu coating on the electrolytic denitrification performance, in this comparative example, only the Ti plate was subjected to the synthesis treatment of Sn coating, and the specific operation steps were consistent with those in Example 3. Then, 250 mL of high-concentration nitrate-organic wastewater (NO3 - -N=5000 mg / L, COD=3000mg / L, NH4 + -N=500 mg / L) was added with a certain amount of 1 mol / L HCl solution to adjust the pH value and conductivity to 3 and 15 mS / cm respectively; then the wastewater, the prepared Ti / Cu-Sn cathode, the ruthenium-iridium-titanium anode and the rotor were placed in a single-chamber electrolytic cell, the positive electrode of the DC power supply was connected to the anode plate, the negative electrode was connected to the cathode plate, the electrode plate spacing was adjusted to 6 mm, the magnetic stirrer speed was set to 450 rpm, the DC power supply was turned on, and the current density was set to 50 mA / cm 2 After that, the reaction started. After 1 hour, the nitrate and COD in the waste liquid were detected (the nitrate detection method refers to GB / T 6912.1-2006, and the COD detection method refers to HJ / T 399-2007). Finally, the nitrate removal rate was 39.24%, the COD removal rate was 77.26%, and the nitrogen selectivity was 93.58%. It can be seen that the nitrate removal rate of the Ti / Sn coated electrode is significantly lower than that of the Ti / Cu-Sn used in Example 3, proving that the Cu / Sn bimetallic coating has a unique performance effect on electrolytic denitrification.

[0043] Comparative Example 4 In order to verify the effect of Cu-Sn coating on the electrolytic denitrification performance, in this comparative example, only the Ti plate was sandpapered and polished, and then electrolytically treated according to Example 4, and finally the nitrate removal rate was 4.84%, the COD removal rate was 68.42%, and the nitrogen selectivity was 97.11%. It can be seen that the pure Ti uncoated electrode can hardly remove nitrate.

[0044] It can be seen from the above comparative examples that pure Ti uncoated electrodes or electrodes containing only one of the metal coatings of Cu and Sn cannot achieve good electrolytic denitrification effects, which proves that the Cu / Sn bimetallic coating has unique performance effects on electrolytic denitrification.

[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A cathode material for catalytic degradation of organic wastewater containing high concentration of nitrates, characterized in that: Its preparation comprises the following steps: 1) After the Ti plate is polished with sandpaper, it is first placed in a 10 wt% NaOH solution for heating and degreasing, and then placed in a 10 wt% oxalic acid solution for heating and surface etching; 2) Apply the copper salt precursor solution evenly to the surface of the etched Ti plate, dry it and then bake it; repeat this process 6 times, rinse it with deionized water and anhydrous ethanol in turn, and wipe the surface with filter paper to ensure that no coating falls off; 3) Using the tin salt precursor solution, the Ti / Cu-Sn multi-metal coating electrode material is prepared according to step 2).

2. The cathode material according to claim 1, characterized in that The heating temperature in step 1) is 60-90° C. and the heating time is 30-180 min.

3. The cathode material according to claim 1, characterized in that The copper salt precursor solution in step 2) is specifically an ethanol solution of copper nitrate, with a concentration of 0.1-2 mol / L and a coating amount of 0.08 mL / cm 2 .

4. The cathode material according to claim 1, characterized in that In step 2), the drying temperature is 60-120°C and the time is 10-60 min; the calcination temperature is 250-850°C and the time is 10-60 min.

5. The method according to claim 1, characterized in that The tin salt precursor solution in step 3) is prepared by mixing metal tin salt, sodium hypophosphite, thiourea, a complexing agent and concentrated hydrochloric acid, heating and stirring at 60-100 °C for 5-45 min to mix them evenly and then cooling them, wherein the concentrations of metal tin salt, sodium hypophosphite, thiourea, a complexing agent and concentrated hydrochloric acid are 0.05-2 mol / L, 0.5-3 mol / L, 0.05-1.5 mol / L, 0.01-1 mol / L and 0.1-1 mol / L, respectively; the application amount of the tin salt precursor solution is 0.04 mL / cm 2 .

6. The method according to claim 5, characterized in that The metal tin salt is selected from one of stannous chloride, tin chloride, trimethyltin chloride and stannous sulfate; the complexing agent is selected from one of sodium citrate, ascorbic acid, sodium bicarbonate and glucose.

7. Use of the electrode material as claimed in claim 1 in electrochemical catalytic degradation of organic wastewater containing high concentration of nitrates, characterized in that: The electrode material is used as the cathode to construct an electrolytic cell. - Under the conditions, it is used in NO3 - And COD is degraded simultaneously, and hydrogen is produced in conjunction.

8. The use according to claim 7, characterized in that: The electrolytic cell uses one of a Pt electrode, an iridium-tantalum-titanium electrode, a ruthenium-iridium-titanium electrode, and a nickel plate electrode as an anode.

9. The use according to claim 7, characterized in that: Before electrolysis, 1-12 mol / L HCl solution was used to adjust the pH of the waste liquid to 0.5-3, and the conductivity was 15-45 mS / cm.

10. The use according to claim 7, characterized in that The wastewater contains NO3 - Concentration ≤10000 mg / L, COD concentration ≤5000 mg / L.

Citation Information

Patent Citations

  • Method for effectively removing nitrate in underground water by using Zn / Cu / Ti multi-metal nanoelectrode

    CN105858818A

  • Cu-Sn-Bi electrode with high catalytic activity, and preparation method and application thereof

    CN108467091A

  • Method for removing nitrate nitrogen through catalytic electrolysis of Cu / Zn electrode

    CN113371796A

  • Sectional type electrochemical nitrate nitrogen removal method

    CN116062845A

Cited By

  • Electro-catalysis electrode for treating high-salt and high-ammonia-nitrogen wastewater and application of electro-catalysis electrode

    CN121317965A

  • Bi / Fe-N-C modified foamy copper electrode, preparation and application in removal of total nitrogen in chlorine-containing wastewater

    CN122079312A